2006
DOI: 10.1001/jama.296.19.2351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Testosterone Replacement Therapy on Prostate Tissue in Men With Late-Onset Hypogonadism

Abstract: These preliminary data suggest that in aging men with late-onset hypogonadism, 6 months of TRT normalizes serum androgen levels but appears to have little effect on prostate tissue androgen levels and cellular functions. Establishment of prostate safety for large populations of older men undergoing longer duration of TRT requires further study. Trial Registration clinicaltrials.gov Identifier: NCT00161304.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
238
0
16

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 375 publications
(263 citation statements)
references
References 64 publications
9
238
0
16
Order By: Relevance
“…[21][22][23] Moreover, among men on androgen depravation therapy for prostate cancer, studies have demonstrated that as men progress from castrate levels (likely unsaturated androgen receptors) toward more physiologic testosterone concentrations, a positive correlation between PSA and serum testosterone is identified. [22][23][24] Additional evidence supporting the androgen receptor saturation hypothesis was recently been provided by Marks et al (2006) 6 who, in landmark randomized, double-blind, placebo-controlled trial analyzed prostate tissue concentrations of the principal androgens of the prostate (testosterone and dihydrotestosterone) following 6 months of parenteral TRT in hypogonadal patients. Despite significant increases in serum testosterone concentrations to normal physiologic levels, researchers identified no significant changes in serum PSA, prostate tissue testosterone and dihydrotestosterone concentrations, or prostate cancer biomarkers and gene expression within the prostate tissue itself.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[21][22][23] Moreover, among men on androgen depravation therapy for prostate cancer, studies have demonstrated that as men progress from castrate levels (likely unsaturated androgen receptors) toward more physiologic testosterone concentrations, a positive correlation between PSA and serum testosterone is identified. [22][23][24] Additional evidence supporting the androgen receptor saturation hypothesis was recently been provided by Marks et al (2006) 6 who, in landmark randomized, double-blind, placebo-controlled trial analyzed prostate tissue concentrations of the principal androgens of the prostate (testosterone and dihydrotestosterone) following 6 months of parenteral TRT in hypogonadal patients. Despite significant increases in serum testosterone concentrations to normal physiologic levels, researchers identified no significant changes in serum PSA, prostate tissue testosterone and dihydrotestosterone concentrations, or prostate cancer biomarkers and gene expression within the prostate tissue itself.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] More contemporary clinical trials have shown little, if consistent evidence of a carcinogenic influence or the tendency to 'unmask' subclinical prostate cancer when TRT is prescribed to otherwise healthy hypogonadal men. [4][5][6] On the basis of lingering concerns and uncertainly, coupled with the fact that the prostate is known to be a androgensensitive organ, most evidence-based clinical guidelines recommend close surveillance of the prostate with prostate-specific antigen (PSA) and digital rectal examination among men treated with TRT. 7,8 Recognizing that PSA remains the most sensitive screening test available for the early detection of prostate cancer, 9,10 a better understanding of the relationship between serum testosterone and PSA levels among men receiving TRT is essential.…”
Section: Introductionmentioning
confidence: 99%
“…131,132 Although endogenous testosterone concentrations are not associated with incidence of prostate cancer, 133 there is also some residual concern over the risk of developing or diagnosing prostate cancer following long-term treatment with testosterone, even though short-term therapy is probably safe in this regard. 131,132,134 Testosterone therapy can be offered to hypogonadal men who meet accepted criteria for the diagnosis of androgen deficiency, with monitoring for efficacy and safety during treatment. 120,130,[135][136][137][138][139] Use of accurate, reliable and validated testosterone assays is important.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 99%
“…By contrast, a variety of studies, using various designs and testosterone formulations, over periods ranging from several months to 15 years, in men with a wide range of ages, have not revealed an increased risk of prostate cancer [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154]. A meta-analysis found that testosterone treatment in older men compared to placebo was not associated with a significantly higher risk of detection of prostate cancer [131], although the frequency of prostate biopsies was much higher in the testosterone-treated group than in the placebo group [131].…”
Section: Lower Urinary Tract Symptoms and Prostate Diseasementioning
confidence: 98%